2004
DOI: 10.1002/jnr.20321
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular mechanisms of neuroprotection by vascular endothelial growth factor

Abstract: The present view of the neuroprotective functions and mechanisms of action of vascular endothelial growth factor (VEGF) is based on studies of neuronal ischemic/hypoxic models in vivo and in vitro. Endogenous neuronal VEGF increases in the ischemic brain and plays a neuroprotective role in the pathophysiologic processes that follow stroke. Exogenous VEGF, directly administered or overexpressed by gene delivery into rat brains, reduces ischemic brain infarct and decreases hypoxic neuronal death. The main neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 31 publications
3
97
0
1
Order By: Relevance
“…However, the effects of long-term VEGF inhibition in the eye will require close monitoring. The constitutive expression of VEGF and its receptors in normal adult neuroretina and choriocapillaris (Kim et al, 1999) suggests that it plays an important role in the survival of neuronal as well as vascular elements, and evidence supporting the neuroprotective effects of VEGF continues to emerge (Storkebaum et al, 2005;Sun and Guo, 2007). There are concerns, for example, that long-term suppression of the survival effects of VEGF may serve to promote geographic atrophy in lieu of neovascular AMD.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, the effects of long-term VEGF inhibition in the eye will require close monitoring. The constitutive expression of VEGF and its receptors in normal adult neuroretina and choriocapillaris (Kim et al, 1999) suggests that it plays an important role in the survival of neuronal as well as vascular elements, and evidence supporting the neuroprotective effects of VEGF continues to emerge (Storkebaum et al, 2005;Sun and Guo, 2007). There are concerns, for example, that long-term suppression of the survival effects of VEGF may serve to promote geographic atrophy in lieu of neovascular AMD.…”
Section: Future Directionsmentioning
confidence: 99%
“…VEGF signaling through its receptors is best characterized in endothelial cells in which Flk-1 activates ERK and PI3K signaling pathways, stimulating cell proliferation and survival [26]. Beyond endothelial cells, research from ischemia/hypoxia models have demonstrated that the neuroprotective actions of VEGF in the brain are mediated by modulation of PI3K pathways, inhibition of ischemia-induced neuronal apoptosis via caspase-3 inhibition, and by enhancing proliferation and migration of neural progenitors (for review, see [27]). In addition to its regulation of endothelial cells and blood vessel formation/permeability, it is clear VEGF has taken a new role in the brain, as a true neurotrophic factor.…”
Section: Vegf In the Central Nervous System: Beyond Angiogenesismentioning
confidence: 99%
“…VEGF increases endothelial cell proliferation, migration, and angiogenesis after stroke; it also modulates the PI3K-AKT-nuclear factor kappa B signaling pathway, inhibits caspase-3 activity, and reduces ischemic neuronal apoptosis. 109,110 However, early postischemic (1 hour) administration of recombinant human VEGF165 (rh-VEGF165) to ischemic rats increased BBB leakage and infarction volume in the ischemic brain. 111 In contrast, late (48 hours) administration of rhVEGF165 to ischemic rats enhanced angiogenesis in the ischemic penumbra and significantly improved neurological recovery, 111 and combination ANG1-VEGF treatment decreased BBB leakage and promoted angiogenesis.…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%
“…115 VEGF increases ischemia-induced tyrosine phosphorylation of Kv1.2 potassium channel proteins via activation of the PI3K pathway, enhances proliferation and migration of neural progenitors in the SVZ, and improves striatal neurogenesis, neuronal differentiation, and maturation of neuroblasts in adult rat brains after stroke. 109,116,117 VEGF can be induced in ischemic brain by both cellbased and pharmacological restoration therapies. In most preclinical and clinical studies, however, the introduction of these factors as single agents has resulted in the formation of stabilized blood vessels of only limited duration.…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%